Jihadi in Southeast Asia: A Comparative Deradicalisation Processbetween Indonesia and the Philippines - Wirawan, Rendy (Interdependence Journal of International Studies, 2020)
Southeast Asia has been a fertile region for the homegrown terrorist groups and lone-wolf terrorists. Some are independently operated, while the others are affiliated with global terrorist network. With many attacks omnipresent in most of Southeast Asian countries, terrorist networks are gradually get revealed and members are arrested with various punishment even to death penalty. During detention, many terrorists, or jihadis, perform progressive development toward moderate understanding of Islam, while others remain unchanged. This article attempts to discover how some jihadis convert their orthodox belief and uncover their motivation to do so. To explore this inquiry, the article will specifically investigate two countries in Southeast Asia where terrorist groups are pervasive, they are Indonesia and the Philippines. The analysis will focus on deradicalisation process that these two countries have designed for their detained jihadis. At the end, we will find that deradicalisation works in Indonesia but not for the Philippines.